Caveolin-1 in oncogenic metabolic symbiosis - Raudenska, Martina; Gumulec, Jaromir; Balvan, Jan; Masarik, Michal (International journal of cancer, 2020)
Metabolic phenotypes of cancer cells are heterogeneous and flexible as a tumor mass is a hurriedly evolving system capable of constant adaptation to oxygen and nutrient availability. The exact type of cancer metabolism arises from the combined effects of factors intrinsic to the cancer cells and factors proposed by the tumor microenvironment. As a result, a condition termed oncogenic metabolic symbiosis in which components of the tumor microenvironment (TME) promote tumor growth often occurs. Understanding how oncogenic metabolic symbiosis emerges and evolves is crucial for perceiving tumorigenesis. The process by which tumor cells reprogram their TME involves many mechanisms, including changes in intercellular communication, alterations in metabolic phenotypes of TME cells, and rearrangement of the extracellular matrix. It is possible that one molecule with a pleiotropic effect such as Caveolin-1 may affect many of these pathways. Here, we discuss the significance of Caveolin-1 in establishing metabolic symbiosis in TME.
Keywords: Neoplasms; regulace genové exprese u nádorů; Gene Expression Regulation, Neoplastic; nádory; nádorové mikroprostředí; Cell Communication; Humans; Tumor Microenvironment; lidé; symbióza; Caveolin 1; Symbiosis; mezibuněčná komunikace; kaveolin 1